Impact assessment of battery energy storage systems towards achieving sustainable development goals - Hannan M.A.; Al-Shetwi A.Q.; Begum R.A.; Jern Ker P.; Rahman S.A.; Mansor M.; Mia M.S.; Muttaqi K.M.; Dong Z.Y. (Elsevier Ltd, 2023)
Battery storage; Electric vehicles; Energy policy; Environmental protection; Planning; Secondary batteries; Solar cells; Sustainable development; Battery energy storage systems; Electric vehicle climate change; Energy; Global demand; Impact assessments; Power sector; Renewable energies; Sustainable development goal; System impact; Transport sectors; Climate change